Phytochemical and Pharmacological Activities of Three Colors Fruit (Eugenia Uniflora L) As Antidiabetes and Antibacteries - Santoso, Puguh; Udayani, Ni Nyoman Wahyu; Putra, I Made Agus Sunadi; Yuwono, Moch. (Budapest International Research and Critics University, 2021)
Eugenia uniflora with local name Indonesia Dewandaru is a plant of the family Myrtaceae. It has green, orange, red, to blackish purple fruits which is widespread in South America, Asia, Africa and Australia. E. uniflora can be used as traditional medicine. The fruits is parts of plants that are widely used in various field nutrition, cosmetic and health, . The active secondary contained in this fuits were applied in anti inflammatory, anti diabetic, adstringent and antioxidant. Several active compounds found in fruits such a carotene esensial oil and polyphenols have been reported to have some biological activities such as antioxidant antidiabetic and antibacterial. The level maturity of fruits level is related to the contend of secondary metabolites such a fenoloic, carotene esential oils. The color of E. uniflora fruit is related to the active phytochemical content and antioxidant activity. Three colors of E. uniflora fruit contain beta carotene and phenolic compounds, essential oil, the highest content of phenolic compounds and antioxidants is found in purple fruit This review provides insight into the effort of discovery and development of pharmaceutical agents derived from fruits of Dewandaru (Eugenia uniflora) plants to make product.